2013
DOI: 10.15361/2175-0106.2013v29n4p33
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa De Anticorpos Anti-Leptospíricos Em Bubalinos / Leptospiral Antibodies in Buffaloes

Abstract: A leptospirose é uma zoonose cosmopolita causada por micro-organismos do gênero Leptospira que pode comprometer a higidez do rebanho, causando sintomatologia clínica, problemas reprodutivos e queda na produção animal. Os animais são hospedeiros naturais dos diferentes sorovares da Leptospira sp., podendo disseminar a infecção para outros animais e humanos por meio da urina. Entre Australis 15,9 % (14/88), com títulos variáveis de 100 a 3200. Esse estudo evidenciou a ocorrência de anticorpos para diferentes sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this region, serological studies have revealed the presence of anti-Leptospira spp. antibodies in buffaloes, with a prevalence ranging from 34.37 to 80.0% and predominance of the Sejroe serogroup (13)(14)(15), similar to what is observed in cattle. Nevertheless, there have been few studies on leptospirosis in buffaloes; thus, the aim of this study was to detect and perform the molecular characterization of Leptospira spp.…”
Section: Introductionsupporting
confidence: 73%
“…In this region, serological studies have revealed the presence of anti-Leptospira spp. antibodies in buffaloes, with a prevalence ranging from 34.37 to 80.0% and predominance of the Sejroe serogroup (13)(14)(15), similar to what is observed in cattle. Nevertheless, there have been few studies on leptospirosis in buffaloes; thus, the aim of this study was to detect and perform the molecular characterization of Leptospira spp.…”
Section: Introductionsupporting
confidence: 73%
“…Hardjo serovar was the third most frequent serovar between seropositive buffaloes in the state of Paraná, with 23.00% (49/213) seroreagent animals for this serovar. Some studies consider this the most frequent serovar found in bubaline herds in Brazil, with a prevalence of 43.4% (165/381) and 33.6% (51/152) in São Paulo (Langoni et al 1999, Favero et al 2002, 23,25% (20/86) and 76,44% (2901/3795) in Pará (Silva et al 2009, Dias et al 2014 in Pernambuco (Oliveira et al 2018), and 20.4% (18/88) in Marajó Island (Oliveira et al 2013). Thus, the prevalence of Hardjo serovar in bubaline from the state of Paraná can be considered lower than in other states and regions of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis is a zoonosis caused by gram-negative bacteria of the genus Leptospira spp. belonging to the family Leptospiraceae, of the order Spirochetales (Adler & de la Peña 2010, Oliveira et al 2013, Pimenta et al 2019). The bacteria have several pathogenic serovars, whose distribution varies according to region, climate and susceptible hosts (Levett 2004, Balamurugan et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation